Joyful learning strategy using game method of treasure clue to improve reading comprehension skill - Vina Anggia Nastitie Ariawan; Inne Marthyane Pratiwi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2017)
The objectives of this research are (1) to describe steps in the implementation of joyful learning strategy using game method of treasure clue to improve reading comprehension skill for the fourth grade students of elementary school; (2) to improve reading comprehension skill for the fourth grade students of elementary school by implementing joyful learning strategy using game method of treasure clue. This research is collaborative Classroom Action Research (CAR) and implemented within two cycles. Each cycle implemented within two meetings. This research impelemented at one of elementary school in Kuningan. Subjects of this research are 31 students of the fourth grade of elementary school. Techniques of collecting data were observation, interview, an document analysis. Data were analyzed using thematic analysis meanwhile data were validated using triangulation, member checking, and reflectivity. The results of this research show that joyful learning strategy using game method of treasure clue can increase students’ reading comprehension skill . The results proved by the increase of reading comprehension outcomes in each cycles. Passing grade percentage of students result in the first cycle is 73,86% and in the second cycle is 87,56%. Therefore, students’ learning outcomes has passed performance indicator research of 85%. The conclusion of this research is the implementation of joyful learning strategy using game method of treasure clue can improve reading comprehension skill for the fourth grade students of elementary school.